2010
DOI: 10.1089/dia.2009.0193
|View full text |Cite
|
Sign up to set email alerts
|

Self-Injection of Insulin Using Appropriate Supportive Devices in Handicapped Subjects with Diabetes

Abstract: Existing or newly manufactured supportive devices can enable handicapped subjects to self-inject insulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“… 3 reported that initial treatment using insulin or an α‐glucosidase inhibitor (αGI) was a risk factor for early non‐persistence and the discontinuation of treatment 3 . Recently, we reported that existing or newly manufactured supportive devices can enable handicapped patients to self‐inject insulin, and this delivery route might improve adherence to insulin treatment 4 . At least three reasons exist for the poor adherence to αGI treatment: (i) the need to take the medicine just before meals; (ii) adverse gastrointestinal effects; and (iii) the need to take the medicine three times a day.…”
Section: Introductionmentioning
confidence: 99%
“… 3 reported that initial treatment using insulin or an α‐glucosidase inhibitor (αGI) was a risk factor for early non‐persistence and the discontinuation of treatment 3 . Recently, we reported that existing or newly manufactured supportive devices can enable handicapped patients to self‐inject insulin, and this delivery route might improve adherence to insulin treatment 4 . At least three reasons exist for the poor adherence to αGI treatment: (i) the need to take the medicine just before meals; (ii) adverse gastrointestinal effects; and (iii) the need to take the medicine three times a day.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin administration is usually performed by various pens [20]. Supportive devices might be helpful for handicapped patients [21].…”
Section: Application Of Insulinmentioning
confidence: 99%